Impact of exogenous GABA treatments on endogenous GABA metabolism in anthurium cut flowers in response to postharvest chilling temperature - Aghdam, Morteza Soleimani (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.